Using video in teacher education - Jo Towers (The Canadian Network for Innovation in Education (CNIE), 2007)
This paper draws on a research study of elementary- and secondary-route preservice teachers in a two-year, after-degree teacher preparation programme. The paper includes excerpts of classroom data, taken from the author's own university classroom, demonstrating preservice teachers' responses to carefully selected video extracts of children learning mathematics in a high-school class also taught by the author. The paper includes commentary on some of the advantages and limitations of video as a teaching tool, develops an argument for the increased use, in both preservice teacher education and inservice teacher professional development, of videotaped episodes that focus on the learners rather than on the classroom teacher, and explores the value of having the teacher whose classroom is featured on the videos present for the discussion of the episodes. The paper explores the potential offered by video material to foster the belief that teaching is a learning activity by (i) refocusing attention on the learner rather than the teacher in the analysis of classroom practices, (ii) raising awareness of the importance of reflective practice, and (iii) providing a prompt for the imaginative rehearsal of action. Résumé : Le présent article se fonde sur une étude technique portant sur des stagiaires des niveaux primaire et secondaire dans un programme de préparation à l'enseignement de deux ans après l'obtention du diplôme. L'article comprend des extraits de données en salle de classe qui proviennent de la salle de classe de l'université de l'auteur même, illustrant les réponses des stagiaires à des extraits vidéo choisis avec soins, extraits portant su des enfants apprenant les mathématiques dans une classe du secondaire dont l'enseignant est l'auteur. L'article comporte des commentaires sur certains des avantages et limites du vidéo comme outil d'enseignement, il présente un argument pour l'augmentation accrue, à la fois pour l'éducation du stagiaire et le perfectionnement professionnel de l'enseignant qualifié, des épisodes sur cassette vidéo qui mettent l'accent sur les apprenants plutôt que sur les enseignants en salle de classe et examine s'il est intéressant que soit présent au moment de la discussion sur les épisodes l'enseignant dont la salle de classe figure sur le vidéo. L'article analyse le potentiel du matériel vidéo appuyant la croyance selon laquelle l'enseignement est une activité d'apprentissage en (i) mettant l'accent sur l'apprenant plutôt que sur l'enseignant dans l'analyse des pratiques d'une salle de classe, (ii) en effectuant une sensibilisation relativement à l'importance de la pratique réflexive et (iii) en guidant la répétition novatrice de la mesure.